Mitochondrial DNA copy number in whole blood and glioma risk: A case control study. Issue 12 (12th January 2016) - Shen, Jie; Song, Renduo; Lu, Zhimin; Zhao, Hua
Abstract : Alterations in mitochondrial DNA (mtDNA) copy number are observed in human gliomas. However, whether variations in mtDNA copy number in whole blood play any role in glioma carcinogenesis is still largely unknown. In current study with 395 glioma patients and 425 healthy controls, we intended to investigate the association between mtDNA copy number in whole blood and glioma risk. Overall, we found that levels of mtDNA copy number were significantly higher in glioma cases than healthy controls (mean: 1.48 vs. 1.32, P  < 0.01). In both cases and controls, levels of mtDNA copy number were inversely correlated with age ( P  < 0.01, respectively). And in cases, newly diagnosed, glioblastoma (GBM), and high grade glioma patients had significantly lower mtDNA copy number than their counterparts ( P  = 0.02, P  < 0.01, and P  = 0.04, respectively). In the multivariate analysis, elevated mtDNA copy number levels were associated with a 1.63‐fold increased risk of glioma (adjusted odds ratio (OR) = 1.63, 95% confidence interval (CI) = 1.23–2.14). In further quartile analysis, study subjects who had highest levels of mtNDA copy number had 1.75‐fold increased risk of gliomas (adjOR = 1.75, 95%CI = 1.18–2.61). In brief, our findings support the role of mtDNA copy number in the glioma carcinogenesis. © 2016 Wiley Periodicals, Inc.